Transgenics, toxicity and therapeutics in rodent models of mutant SOD1-mediated familial ALS. - Turner, B; Talbot, K (2008)
Gain-of-function mutations in the Cu,Zn-superoxide dismutase (SOD1) gene are implicated in progressive motor neuron death and paralysis in one form of inherited amyotrophic lateral sclerosis (ALS). At present, transgenic expression of 12 human SOD1 mutations driven by the endogenous promoter is disease-causative and uniformly lethal in mice and rats, despite tremendous biochemical and biophysical variation between the mutants tested. This contrasts with the subclinical motor neuron disease phenotypes of wild-type SOD1 transgenic and knockout mice. Molecular mechanisms such as glutamate-induced excitotoxicity, axonal transport blockade, mitochondrial dysfunction, neuroinflammation and apoptosis triggered by mutant SOD1 catalysed oxidative reactions and/or protein misfolding are proposed to drive ALS pathogenesis. Around 100 genetic cross-breeding experiments with transgenic mutant SOD1 mice have been performed to verify these mechanisms in vivo. Furthermore, mounting evidence from mice with cell restrictive, repressible or chimeric expression of mutant SOD1 transgenes and bone marrow transplants supports non-neuronal origins of neuroprotection in ALS. Transgenic mutant SOD1 rodents have also provided the benchmark preclinical tool for evaluation of over 150 potential therapeutic anti-oxidant, anti-aggregation, anti-glutamatergic, anti-inflammatory, anti-apoptotic and neurotrophic pharmacological agents. Recent promising findings from gene and antisense therapies, cell replacement and combinatorial drug approaches in transgenic mutant SOD1 rodents are also emerging, but await successful translation in patients. This review summarises the wealth of known genetic and therapeutic modifiers in rodent models with SOD1 mutations and discusses these in the wider context of ALS pathoetiology and treatment.